Measuring Teachers' Writing Assessment Literacy: a Case Study of Universitas Singaperbangsa Karawang - Nia Pujiawati; Januarius Mujiyanto; Rudi Hartono; Issy Yuliasri (International Conference on Science, Education, and Technology, 2021)
Considerable amounts of students and graduates of universities were found to be deficient in writing English. To this end, several researchers have focused so far exclusively on investigating teaching and learning methodologies in the classroom, while teachers have remained untouched in their capacity for evaluation and assessment. Empirical evidence suggested that assessment activities affect students' performance. As assessment literacy should begin with an examination of its knowledge domain, this study attempts to gauge the teacher's level of writing assessment literacy by distributing a questionnaire adopted from the Language Assessment Knowledge Scale (LAKS). The findings suggested that most of the teachers have a low level of literacy in writing assessment.